Corporate social responsibility and corporate governance in Malaysian government-linked companies - Esa, Elinda; Mohd Ghazali, Nazli Anum (Emerald Group Publishing Limited, 2012)
Purpose – The purpose of this paper is to investigate whether there has been a change in the level of corporate social responsibility (CSR) disclosure and to determine whether corporate governance attributes influence CSR disclosure in corporate annual reports of Malaysian government-linked companies (GLCs).